Analisis komparatif Kurikulum Merdeka dan KSSM Malaysia dalam literasi matematika - Nadya Irba Rosyadah; Artika Nur Noviani; Ika Kurniasari (Curricula: Journal of Curriculum Development, 2026)
Mathematical literacy is a crucial skill in the 21st century, helping people understand and apply Mathematics in everyday life. However, the results of the PISA 2022 show that Indonesia and Malaysia still have mathematical literacy skills below the OECD average. To address this issue, Indonesia began implementing the Kurikulum Merdeka in 2022, while Malaysia has been using the Kurikulum Standar Sekolah Menengah (KSSM) since 2017. This study aims to compare the two curricula for improving mathematical literacy by analyzing official documents, academic articles, and international reports. The study results show that both curricula focus on problem-solving, analytical thinking, and the application of Mathematics in real-world situations. However, the Independent Curriculum emphasizes greater freedom to improve mathematical literacy through teacher analysis, project-based learning, and a student-centered approach. On the other hand, the KSSM has a more structured learning system that incorporates Higher-Order Thinking Skills (HOTS) and a standardized numeracy program. These differences can serve as a reference for improving the quality of Mathematics education in Southeast Asia.